METHODOLOGICAL MODEL OF DIFFERENTIAL EDUCATION IN TEACHING PHYSICS - Obidjon Elamonovich Imomov (Scholar Express Journals, 2021)
This article outlines the methodological system of differential education in physics for undergraduate students of technical disciplines, the construction of nonlinear learning trajectories. Methodological model of construction of nonlinear learning trajectories in the project activities of education on the basis of a differential approach to future engineers provides the principles of development of general professional and general cultural competencies in its implementation
Keywords: Paradigm; innovative education; nonlinear learning trajectories; methodology